THE LINGUISTIC DESCENT OF AMBITION: EXPLORING POWER, CONFLICT, AND DESPAIR IN MARLOWE’S DOCTOR FAUSTUS - Krishna, Kota Sai; Madhavi, P. Asha; Seshagiri, H (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article explores the linguistic and thematic evolution of Christopher Marlowe’s Doctor Faustus, focusing on the interplay of language and character development to illuminate the protagonist’s psychological, moral, and spiritual transformation. By analysing eight key linguistic elements—modal verbs, temporal constructs, rhetorical questions, pronoun shifts, repetition, hyperbole, imperative language, and oppositional constructs—the study reveals how Marlowe captures Faustus’s descent from confident ambition to existential despair. Each linguistic feature is linked to specific acts and scenes, highlighting the gradual progression of Faustus’s internal conflict, moral struggles, and eventual realisation of eternal damnation. The analysis demonstrates how modal verbs reflect Faustus’s declining agency, while temporal constructs underscore the tension between fleeting pleasures and the permanence of damnation. Rhetorical questions and oppositional language externalise his internal conflict, allowing audiences to engage with his moral dilemmas. Pronoun shifts and hyperbole reflect his psychological fragmentation and emotional extremes, while repetition and imperative language heighten the dramatic intensity of his despair. By interweaving these linguistic elements, Marlowe offers a profound exploration of ambition, accountability, and divine justice. This study positions Doctor Faustus as a timeless work that transcends its historical context, offering insights into human ambition, moral conflict, and the tragic consequences of overreaching desire.